2022
DOI: 10.1155/2022/5666067
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Study of Different Treatment Methods for Tuberculous Pleuritis Complicated with Pleural Tuberculoma

Abstract: Objective. To compare the clinical efficacy and adverse drug reactions of four different schemes in the treatment of pleural tuberculoma. Methods. A total of 120 patients with pleural tuberculoma admitted to the Tuberculosis Department of our hospital from January 2018 to January 2021 were selected as the research subjects. According to different treatment methods, the patients were divided into four groups, with 30 cases in each group. They were as follows: group A received classical HRZE regimen, group B rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%